2016
DOI: 10.1007/s00128-016-1814-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Synthetic Musks in Sediments of Yellow River Delta Wetland, China

Abstract: In this study, seven kinds of synthetic musks were characterized in sediment samples of Yellow River Delta wetland, including celestolide, phantolide, traseolide, galaxolide, tonalide, musk xylene, and musk ketone. They were analyzed using gas chromatography-mass spectrometry (GC-MS), with recoveries of 91.85 %-105.35 % and the relative standard deviation (% RSD) were 3.30 %-8.11 % for all analytes. Galaxolide and tonalide were the main musk contaminants which were detected in sediment samples. The total conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The frequency of detection for this xenobiotic in this site (100%) was similar to that found in CB. However, Li et al (2014) reported lower concentrations of this musk in sediments from Meiliang Bay, Taihu Lake (China) (range 0.27-0.79 ng/g), as also occurred in sediments collected in Yellow River, China (range 1.42-8.60 ng/g, mean 2.92 ng/g) (Lou et al (2016). In CB, the concentrations of fragrances tended to be higher at stations S1 and S2, which indicated that these are point sources of Galaxolide and OTNE pollution.…”
Section: Discussionmentioning
confidence: 96%
“…The frequency of detection for this xenobiotic in this site (100%) was similar to that found in CB. However, Li et al (2014) reported lower concentrations of this musk in sediments from Meiliang Bay, Taihu Lake (China) (range 0.27-0.79 ng/g), as also occurred in sediments collected in Yellow River, China (range 1.42-8.60 ng/g, mean 2.92 ng/g) (Lou et al (2016). In CB, the concentrations of fragrances tended to be higher at stations S1 and S2, which indicated that these are point sources of Galaxolide and OTNE pollution.…”
Section: Discussionmentioning
confidence: 96%
“…The concentrations of UV-filter such a homosalate, octisalate, and benzophenone-3 were identified in the parts per trillion ng/l in surface seawater and in μg/kg in sediment and corals from Hawaii. Lou et al (2016) detected seven kinds of synthetic musks in sediment samples of the Yellow River Delta wetland, including celestolide, phantolide, traseolide, galaxolide, tonalide, musk xylene, and musk ketone at concentrations of up to 8.6 μg/kg. Liu et al (2018) found residues of 19 types of antibiotics in wild marine fish tissues from Laizhou Bay (China) at concentrations of up to 500 μg/kg.…”
Section: Pharmaceuticals and Personal Care Productsmentioning
confidence: 99%
“…Several studies have described the occurrence of pharmaceuticals and personal care products (such as analgetics, antibiotic, musk compounds, UV filters, and others) in waters, sediments, and animals ranging from ng/kg to mg/kg (Vallecilos et al 2015;Lou et al 2016;Zhang et al 2020). Matongo et al (2015) found residues of antipyretics and antibiotics in the sediment from ponds.…”
Section: Pharmaceuticals and Personal Care Productsmentioning
confidence: 99%